Strategi Persaingan Antar Pedagang dalam Perspektif Sosiologi Ekonomi Di Pasar Blauran Palangka Raya - Helma Ariyani; Dehen Dehen; Sri Rohaetin (Jurnal Syntax Transformation, 2021)
This study aims to 1) know the strategy of competition between traders in The Blauran Market Palangkaraya, 2) know the supporting factors and inhibition of competition between traders in Blauran Market Palangka Raya. The research method used is qualitative descriptive research. Data collection techniques in this study are observations, interviews, documentation. The results showed that: 1) The prevailing strategy in Blauran Palangka Raya Market so far is a competitive strategy between traders with the concept of all buying and selling activities carried out with a strong motivation to earn income in a healthy way by improving the quality of goods or services. 2) Factors that affect competition in the Blauran Palangka Raya market are price borders, quality and varied products, strategic market locations, and promotions. Analysis of Competition Strategy between Traders in The Effectiveness of Economic Sociology in Blauran Palangka Raya Market is conducted by improving the quality of services, and products marketed to increase the turnover of traders. The process of facing competition between traders in Blaura Palangka Raya Market is carried out through solidarity between traders and buyers by focusing on improving the quality of services and products that suit the needs and interests of buyers.